A study on the multidimensional result-oriented capability of professional workers - Prataksita, Narendra; Sasmoko, Sasmoko; Elidjen, Elidjen; Bandur, Agustinus (International Journal of Innovative Research and Scientific Studies, 2023)
An increasing number of freelancers and independent professionals are engaged in short-term and temporary work. There are several studies that define the key intangible resources and abilities of professional employees but there is limited research that examines all of them collectively. Therefore, the aim of this study is to improve our understanding of professional workers' various intangible resources and capabilities by proposing the result-oriented capability (ROC) construct and its subdimensions by analyzing existing literature on knowledge workers, professional employees, psychology and management. The proposed model was empirically tested using the data gathered from 384 professional workers that worked in knowledge-intensive business services (p-KIBS). Construct reliability and validity are analyzed using the IBM Statistical Package for Social Sciences (SPSS) and the Analysis of Moments Structure (AOMS). This research proposes and confirms that ROC has reflective sub-dimensions such as professional expertise, relational capability, operational capability and innovation orientation. The study's findings provide important insights into how to improve professional workers' capabilities. The new measures can be used as diagnostic tools for professional worker recruitment, assessment and training. This can be beneficial for individual professional workers with larger implications for people management, training and development and organizational success.